Beneficial effects of Cichorium intybus L. extract on oxidative status and reproductive parameters in male Wistar rats: An experimental study - Mehran Dorostghoal; Seyyed Mansour Seyyednejad; Marzieh Noroozi Tabrizi Nejad (Shahid Sadoughi University of Medical Sciences, 2019)
Abstract Background During recent years, increasing concern has been raised about the declining sperm count and human male infertility. Cichorium intybus L. (C. intybus) has traditionally been used in Iranian folk medicine as hepato protective and blood purifier and for its presumed fertility-enhancing properties. Objective A dose-response study was performed to determine the effect of C. intybus ethanolic leave extract on the reproductive parameters in adult Wistar male rats. Materials and Methods In this experimental study, 40 healthy adult male Wistar rats (8 wk old, 200-210 gr body weight) were randomly divided (n = 10/each) as control and groups treated with 50, 100, and 200 mg/kg/day of C. intybus extract via gavage for 70 days. Serum hormonal assay, epididymal sperm evaluation, and analysis of morphometrical parameters, antioxidant enzymes, and lipid peroxidation levels of testis were done in each experimental group. Results Weights of testis and epididymis increase significantly in male rats treated with 200 mg/kg C. intybus extract. Sperm density and percent of morphologically normal sperm were significantly increased in a dose-related manner with C. intybus treatment.Serum testosterone was higher at 100 and 200 mg/kg C. intybus extract-treated groups. C. intybus significantly reduced malondialdehyde levels and also increased superoxide dismutase and glutathione peroxidase activity in testicular tissue of rats. Conclusion It is concluded that C. intybus leave extract improves reproductive parameters in male rats which might be a consequence of both its antioxidant and androgenic properties.